2013
DOI: 10.1002/jgrd.50418
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the tropical tropopause layer for equatorial Kelvin wave propagation

Abstract: [1] We analyze the propagation of equatorial Kelvin waves from the troposphere to the stratosphere using a new filtering technique applied to ERA-Interim data (very similar results for Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) temperatures) that allows separation of wave activity into number of waves and wave amplitude. The phase speed of Kelvin waves (order 20 m/s) is similar to the magnitude of zonal wind in the tropical tropopause layer (TTL), and correspondingly, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…7a shows amplitude variations that are strongly modulated by the QBO, with enhanced wave activity in periods of transition from easterly to westerly stratospheric wind (westerly shear zones). Similar results have been found by Randel and Wu (2005); Ern et al (2008); Alexander and Ortland (2010); Flannaghan and Fueglistaler (2013). These peaks in Kelvinwave activity are expected since Kelvin-wave energy is accumulated below the critical level, which is located near the zero-wind line.…”
Section: Temporal Variations In Kelvin-wave Activitysupporting
confidence: 85%
See 3 more Smart Citations
“…7a shows amplitude variations that are strongly modulated by the QBO, with enhanced wave activity in periods of transition from easterly to westerly stratospheric wind (westerly shear zones). Similar results have been found by Randel and Wu (2005); Ern et al (2008); Alexander and Ortland (2010); Flannaghan and Fueglistaler (2013). These peaks in Kelvinwave activity are expected since Kelvin-wave energy is accumulated below the critical level, which is located near the zero-wind line.…”
Section: Temporal Variations In Kelvin-wave Activitysupporting
confidence: 85%
“…This was also found by Ryu et al (2008), who showed that background zonal wind plays an important role in modulating Kelvin waves close to the tropical tropopause. More recently, Flannaghan and Fueglistaler (2013) showed that seasonal and interannual variability of Kelvin-wave propagation is dominated by the variability in the background wind field. However, we have explored this behavior and do not find any evident relationships between Kelvin-wave amplitudes and changes in winds near the tropopause (based on Singapore winds).…”
Section: Temporal Variations In Kelvin-wave Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…With finer vertical resolution (W_L103) the model produces a stronger upwelling in the tropics (and a consistent cooling) up to the tropopause region, with westerly wind anomalies above. This strengthened tropical upwelling cannot continue further up because of the westerly wind anomalies which block the transport into the subtropics (Simpson et al, 2009;Flannaghan and Fueglistaler, 2013). Above the tropical tropopause there is less upwelling and in particular more transport from the subtropics into the tropical TTL, leading to a stronger warming around 19 km in the W_L103 experiment.…”
Section: Changes In the Brewer-dobson Circulationmentioning
confidence: 97%